Lenalidomide and dexamethasone in relapsed/refractory immunoglobulin light chain (AL) amyloidosis: results from a large cohort of patients with long follow-up - Basset, Marco; Kimmich, Christoph; Schreck, Nicholas; Krzykalla, Julia; Dittrich, Tobias; Veelken, Kaya; Goldschmidt, Hartmut; Seckinger, Anja; Hose, Dirk; Jauch, Anna; Müller-Tidow, Carsten; Benner, Axel; et al. (British journal of haematology, 2021)
Lenalidomide and dexamethasone (RD) is a standard treatment in relapsed/refractory immunoglobulin light chain (AL) amyloidosis (RRAL). We retrospectively investigated toxicity, efficacy and prognostic markers in 260 patients with RRAL. Patients received a median of two prior treatment lines (68% had been bortezomib-refractory; 33% had received high-dose melphalan). The median treatment duration was four cycles. The 3-month haematological response rate was 31% [very good haematological response (VGHR) in 18%]. The median follow-up was 56·5 months and the median overall survival (OS) and haematological event-free survival (haemEFS) were 32 and 9 months. The 2-year dialysis rate was 15%. VGHR resulted in better OS (62 vs. 26 months, P < 0·001). Cardiac progression predicted worse survival (22 vs. 40 months, P = 0·027), although N-terminal prohormone of brain natriuretic peptide (NT-proBNP) increase was frequently observed. Multivariable analysis identified these prognostic factors: NT-proBNP for OS [hazard ratio (HR) 1·71; P < 0·001]; gain 1q21 for haemEFS (HR 1·68, P = 0·014), with a trend for OS (HR 1·47, P = 0·084); difference between involved and uninvolved free light chains (dFLC) and light chain isotype for OS (HR 2·22, P < 0·001; HR 1·62, P = 0·016) and haemEFS (HR 1·88, P < 0·001; HR 1·59, P = 0·008). Estimated glomerular filtration rate (HR 0·71, P = 0·004) and 24-h proteinuria (HR 1·10, P = 0·004) were prognostic for renal survival. In conclusion, clonal and organ biomarkers at baseline identify patients with favourable outcome, while VGHR and cardiac progression define prognosis during RD treatment.
Gesehen am 14.08.2023